Isolation and characterisation of thermophilic bacterial isolates producing L-asparaginase - Jimat, Dzun Noraini; Mohamed , Intan Baizura Firda (IIUM Press, 2016)
This procedure is following Gulati, Saxena, and Gupta (1997) protocol which is known as semi-quantitative plate assay for screening L-asparaginase- producing bacterial from local hot spring. The plate agar medium containing asparagine (as sole nitrogen sourse) is prepared with addition of phenol red which later shows an indication of L-asparaginase based on changes of colour. Phenol red at acidic is yellow which might change colour to pink when it is at alkaline. Thus, it indicates the formation of pink zone around microbial colonies producing L-asparaginase. The inoculated agar plates are incubated at 370C in an incubator for 24 hours. Thus, the isolation and screening of bacterial producing L-asparaginase are based on phenol-red zone. After purification, the isolates are characterised using several biochemical tests.